Contamination level, source identification and health risk assessment of potentially toxic elements in drinking water sources of mining and non-mining areas of Khyber Pakhtunkhwa, Pakistan. (11th August 2022) - Bhatti, Zahid Imran; Ishtiaq, Muhammad; Khan, Said Akbar; Nawab, Javed; Ghani, Junaid; Ullah, Zahid; Khan, Sardar; Baig, Shams Ali; Muhammad, Ihsan; Din, Zia Ud; Khan, Asad
Abstract: Accelerated mining activities have increased water contamination with potentially toxic elements (PTEs) and their associated human health risk in developing countries. The current study investigated the distribution of PTEs, their potential sources and health risk assessment in both ground and surface water sources in mining and non-mining areas of Khyber Pakhtunkhwa, Pakistan. Water samples ( n = 150) were taken from selected sites and were analyzed for six PTEs (Ni, Cr, Zn, Cu, Pb and Mn). Among PTEs, Cr showed a high mean concentration (497) μg L −1, followed by Zn (414) μg L −1 in the mining area, while Zn showed the lowest mean value (4.44) μg L −1 in non-mining areas. Elevated concentrations of Ni, Cr and a moderate level of Pb in ground and surface water of Mohmand District exceeded the permissible limits set by WHO. Multivariate statistical analyses showed that the pollution sources of PTEs were mainly from mafic-ultramafic rocks, acid mine drainage, open dumping of mine wastes and mine tailings. The hazard quotient (HQ) was the highest for children relative to that for adults, but not higher than the USEPA limits. The hazard index (HI) for ingestions of all selected PTEs was lower than the threshold value (HIing < 1), except for Mohmand District, which showed a value of HI >1 in mining areas through ingestion. Moreover, the carcinogenic risk (CR) values exceeded the threshold limits for Ni and Cr set by the USEPA (1.0E-04–1.0E-06). In order to protect the drinking water sources of the study areas from further contamination, management techniques and policy for mining operations need to be implemented. HIGHLIGHTS: Elevated Ni, Cr and Pb levels exceeded the WHO permissible limits in ground and surface water. Mafic-ultramafic rocks, acid mine drainage, mine wastes and mine tailings are the main primary factors influencing the distribution of PTEs and their contamination. Health risk was relatively high for children than for adults in mining and non-mining areas. Management policies and monitoring strategies need to be implemented for mining operations. Graphical Abstract